The relationship between dietary branched-chain and aromatic amino acids with the regulation of leptin and FTO genes in adipose tissue of patients undergoing abdominal surgery - Farshad Teymoori; Hossein Farhadnejad; Mostafa Norouzzadeh; Mitra Kazemi Jahromi; Niloufar Saber; Ebrahim Mokhtari; Golaleh Asghari; Emad Yuzbashian; Parvin Mirmiran; Alireza Khalaj; Maryam Zarkesh; Mehdi Hedayati; et al. (Amino Acids)
Abstract Recent studies have suggested that the interaction between diet and an individual’s genetic predisposition can determine the likelihood of obesity and various metabolic disorders. The current study aimed to examine the association of dietary branched-chain amino acids(BCAAs) and aromatic amino acids(AAAs) with the expression of the leptin and FTO genes in the visceral and subcutaneous adipose tissues of individuals undergoing surgery. This cross-sectional study was conducted on 136 Iranian adults, both men and women, aged ≥18 years. The samples were selected from patients admitted for abdominal surgeries. The dietary intake of BCAAs and AAAs was determined using a valid and reliable 168-item food frequency questionnaire. Using the quantitative PCR method, leptin and FTO mRNA expression was measured in both visceral and subcutaneous fat tissues. The mean age of the participants was 39.8 ± 12.7 years, and the mean intake of BCAAs and AAAs was 17.7 ± 0.9 and 9.3 ± 0.3% of protein per day, respectively. In overweight-obese patients(body mass index = 25–34.9 kg/m2), the intake of BCAAs(β:-0.75,95%CI:-1.47,-0.03), valine(β:-0.78,95%CI:-1.51,-0.05), and tyrosine(β:-0.81,95%CI:-1.55,-0.06) was inversely associated with FTO gene expression in subcutaneous fat tissue in adjusted model. In morbidly obese patients(body mass index ≥ 35 kg/m2), a higher intake of total BCAAs(β:1.10,95%CI:0.07–2.13), leucine(β:1.07,95%CI:0.03–2.13), and isoleucine(β:1.49,95%CI:0.46–2.52) was associated with an increase of leptin gene expression in subcutaneous fat tissue. Our findings suggest that dietary BCAA may associated with gene expression in adipose tissues, potentially influencing obesity-related metabolic pathways. Further prospective studies are warranted to validate results and elucidate the potential for dietary interventions targeting amino acids intake in obesity management.